2016
DOI: 10.1038/srep28249
|View full text |Cite
|
Sign up to set email alerts
|

GPS-Lipid: a robust tool for the prediction of multiple lipid modification sites

Abstract: As one of the most common post-translational modifications in eukaryotic cells, lipid modification is an important mechanism for the regulation of variety aspects of protein function. Over the last decades, three classes of lipid modifications have been increasingly studied. The co-regulation of these different lipid modifications is beginning to be noticed. However, due to the lack of integrated bioinformatics resources, the studies of co-regulatory mechanisms are still very limited. In this work, we develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 41 publications
1
96
0
Order By: Relevance
“…The use of structured illumination microscopy (SIM) allowed to localize the wild‐type NLD::citrine signal to what appears to be the plasma membrane of the sperm cells, confirming the results observed in Arabidopsis roots (Fig I and Appendix Fig S5D). An in silico analysis of the wild‐type NLD protein sequence predicted the absence of a signal peptide but the presence of an S‐palmitoylation site at C10 and an S‐palmitoylation or S‐farnesylation site at C423 (Xie et al , ) (Appendix Fig S6). The presence of two lipid anchor sites was coherent with a localization in the plasma membrane and the loss of the C‐terminal lipid anchor in the truncated NLD‐PK6 protein provided a plausible explanation of its mis‐localization.…”
Section: Resultsmentioning
confidence: 99%
“…The use of structured illumination microscopy (SIM) allowed to localize the wild‐type NLD::citrine signal to what appears to be the plasma membrane of the sperm cells, confirming the results observed in Arabidopsis roots (Fig I and Appendix Fig S5D). An in silico analysis of the wild‐type NLD protein sequence predicted the absence of a signal peptide but the presence of an S‐palmitoylation site at C10 and an S‐palmitoylation or S‐farnesylation site at C423 (Xie et al , ) (Appendix Fig S6). The presence of two lipid anchor sites was coherent with a localization in the plasma membrane and the loss of the C‐terminal lipid anchor in the truncated NLD‐PK6 protein provided a plausible explanation of its mis‐localization.…”
Section: Resultsmentioning
confidence: 99%
“…Membrane tethering of IQD proteins is possibly stabilized by S-acylation (or palmitoylation), which attaches fatty acids to internal Cys residues. In silico analyses using the GPS-Lipid and CSS-Palm tools (Ren et al, 2008;Xie et al, 2016) predicted the presence of Sacylation sites in several IQD family members (Supplemental Table S1). Experimental support for the lipidation of IQD proteins is provided by a large-scale proteomics data set, which reported S-acylation of IQD32 (Hemsley et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Ras proteins were widely reported to be the farnesylation targets in eukaryotic cells, so we sought to determine if the functions of M. oryzae Ras proteins are regulated by farnesylation. Some Ras‐like proteins were found in M. oryzae , and they were used to perform farnesylation site prediction by GPS‐Lipid (http://lipid.biocuckoo.org/webserver.php) (Xie et al , ). Six RAS‐like proteins, Ras1, Ras2, rho1, rho2, rho3, rho4 and ced‐10 (Fu et al , ; Zheng et al , ; Zhou et al , ), were found to contain the C‐terminal CaaX motifs (Fig.…”
Section: Resultsmentioning
confidence: 99%